Sociology 290: Chicanos in American Society (Graduate) - Jiménez, Tomás (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course examines the experiences of the Mexican-origin population in the United States, focusing on the theories that explain these experiences. We begin by looking at the origins of this population in the United States. We will pay particular attention to the Mexican immigrant experience and the features that make this immigrant experience unique, relative to other groups. We will, then, shift our focus to examine the experiences of the American-born, Mexican-origin population, examining the experiences of the second-generation and the established, latter-generation Mexican Americans. We will end the course by considering the place of the Mexican-origin population in American’s racial and ethnic landscape.